2022
DOI: 10.3389/fdmed.2022.833191
|View full text |Cite
|
Sign up to set email alerts
|

An Application of Machine Learning Techniques to Analyze Patient Information to Improve Oral Health Outcomes

Abstract: ObjectiveVarious health-related fields have applied Machine learning (ML) techniques such as text mining, topic modeling (TM), and artificial neural networks (ANN) to automate tasks otherwise completed by humans to enhance patient care. However, research in dentistry on the integration of these techniques into the clinic arena has yet to exist. Thus, the purpose of this study was to: introduce a method of automating the reviewing patient chart information using ML, provide a step-by-step description of how it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Diagram of the SGSSS and Proposal to Establish Oral Health Networks (in Spanish) Additionally, and as a differentiating factor to give them a competitive advantage, all administrative and clinical processes must be conducted through ICTs that allow data digitalization and, ideally, automation through articial intelligence, machine learning, and data mining. In this way, better results would also be achieved in diagnostic processes (52)(53) and operational and personnel costs would be reduced in order to have a nancial balance.…”
Section: Discussionmentioning
confidence: 99%
“…Diagram of the SGSSS and Proposal to Establish Oral Health Networks (in Spanish) Additionally, and as a differentiating factor to give them a competitive advantage, all administrative and clinical processes must be conducted through ICTs that allow data digitalization and, ideally, automation through articial intelligence, machine learning, and data mining. In this way, better results would also be achieved in diagnostic processes (52)(53) and operational and personnel costs would be reduced in order to have a nancial balance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, AI models can be trained to detect subtle changes in images over time, which may be indicative of the disease progression. Ameli et al [ 145 ] used ordinal logistic regression and artificial neural networks to determine predictive relationships between the extracted patient chart data topics and oral health-related contributors; the authors observed that the risk for carious lesions, occlusal risk, biomechanical risk, gingival recession, periodontitis, and gingivitis were highly predictable using the extracted radiographic and treatment planning topics and chart information [ 145 ].…”
Section: Ai In Dentistrymentioning
confidence: 99%